STRATEGI PENGEMBANGAN PADA PERSPEKTIF NONKEUANGAN METODE BALANCE SCORECARD TERHADAP PENINGKATAN KINERJA KEUANGAN UMKM DI INDONESIA SAAT PANDEMIC COVID-19 - Juan Carlos Pangestu (POLITEKNIK LP3I JAKARTA, 2021)
The purpose of this study is to determine and analyze: how much the company's business strategy has an influence on improving company performance and how big is the role of management accounting strategy in moderating the relationship between the company's business strategy and improving company performance. This research has its own peculiarities and is unique because it was carried out when the world situation was experiencing the corona pandemic, including Indonesia. Data were collected using quantitative techniques from primary data sources collected from questionnaires distributed to several restaurants, canteens and beverage outlets in the Jakarta and Bandung areas, especially in the food and beverage sector. Based on the test result using multiple linear regression, this study concludes that: (1) The customer perspective has a significant influence on the financial performance of MSMEs in Indonesia, (2) the Internal Business Process perspective has a significant influence on the financial performance of MSMEs in Indonesia, and ( 3) Learning and Growth Perspective has a significant influence on the financial performance of MSMEs in Indonesia.Keywords: customer perspective, internal business process perspective, learning and growth perspective, financial performance